2022
DOI: 10.1109/access.2022.3144076
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomous Platforms Inertial Dataset

Abstract: One of the critical tasks required for fully autonomous functionality is the ability to achieve an accurate navigation solution; that is, to determine the platform position, velocity, and orientation. Various sensors, depending on the vehicle environment (air, sea, or land), are employed to achieve this goal. In parallel to the development of novel navigation and sensor fusion algorithms, machine-learning based algorithms are penetrating into the navigation and sensor fusion fields. An excellent example for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The stationary conditions field experiment dataset is based on a dataset published in [53]. There, a unique device, as shown in Figure 9 was built to align between a Huawei P40 smartphone and an Inertial Lab MRU-P unit [54].…”
Section: B Field Experiments Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The stationary conditions field experiment dataset is based on a dataset published in [53]. There, a unique device, as shown in Figure 9 was built to align between a Huawei P40 smartphone and an Inertial Lab MRU-P unit [54].…”
Section: B Field Experiments Datasetmentioning
confidence: 99%
“…Here, noisy samples are given by a consumergrade smartphone sensor, whose readings are submerged in lower levels of stochastic noise but higher bias levels, as smartphones can be prone to mechanical shocks that impair the orthogonality of the sensor axes. In contrast, the GT references are taken from a high-end sensor, whose accurate measurements are characterized by significantly lower noise levels [53]. In other words, the generalization task here is to find an approximation function that mimics best the GT sensor.…”
Section: B Experimental Assessmentmentioning
confidence: 99%
“…To evaluate QuadNet's performance relative to the QDR approach, the same dataset as in [19] was used. This dataset was recently published in the autonomous platforms inertial dataset [43] and is available at https://github.com/ansfl/Navigation-Data-Project/, accessed on 22 December 2020.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
“…The dataset was created by collecting DVL data from nine different missions performed by the AUV with a total time duration of 13,886 seconds, which translates to the same number of DVL measurements and 1,388,600 IMU measurements. This dataset is described in Shurin et al (2022) and can be found on https://github.com/ansfl/Navigatio n-Data-Project/. Each of the missions had different parameters regarding the length of the mission, the objective, the speed of the AUV, the depth of the AUV, and the maneuvers it performed.…”
Section: Auv Sea Experimentsmentioning
confidence: 99%
“…In parallel to the developments in underwater navigation, data-driven approaches show great results in different fields to improve navigation accuracy and robustness. In Shurin, Saraev, Yona, Gutnik, Faber, Etzion and Klein (2022) deep hybrid learning approach was implemented to improve quadrotor dead reckoning. In the field of indoor navigation with pedestrian dead reckoning, learning frameworks showed superior results over model-based approaches Gu, Khoshelham, Yu and Shang (2018); Chen, Zhao, Lu, Wang, Markham and Trigoni (2020); Asraf, Shama and Klein (2021).…”
Section: Introductionmentioning
confidence: 99%